2021
DOI: 10.46325/gabj.v4i3.135
|View full text |Cite
|
Sign up to set email alerts
|

Yield stability and test location representativeness in foxtail millet [Setaria italica (L.) Beauv.] genotypes

Abstract: Development of a crop variety with high grain yield and stability in test locations is an important part of crop breeding program. Thirteen foxtail millet genotypes were evaluated in randomized complete block design with three replications in Jumla and Dolakha, Nepal from April to August in three consecutive years 2017, 2018, and 2019. The objective of this study was to analyze grain yield stability and adaptability of foxtail millet genotypes applying genotype main effect plus genotype by environment interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The variance due to pooled deviation was found significant for hulling (%), chlorophyll content (mg 100 g -1 fresh weight), leaf area (cm 2 ), protein content (%), crude fiber (%), mineral matter (mg 100 g -1 ), iron content (mg 100 g -1 ), calcium content (mg 100 g -1 ) and ash content (mg 100 g -1 ). Highly significant differences among genotypes, environments and G×E interaction were reported by Fentie et al (2013), Soodet al (2018 and Kandel et al (2020). The environmental indices computed for the quality characters studied were presented in Table 2 indicating both the favourable and unfavourable environments for all the component characters.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The variance due to pooled deviation was found significant for hulling (%), chlorophyll content (mg 100 g -1 fresh weight), leaf area (cm 2 ), protein content (%), crude fiber (%), mineral matter (mg 100 g -1 ), iron content (mg 100 g -1 ), calcium content (mg 100 g -1 ) and ash content (mg 100 g -1 ). Highly significant differences among genotypes, environments and G×E interaction were reported by Fentie et al (2013), Soodet al (2018 and Kandel et al (2020). The environmental indices computed for the quality characters studied were presented in Table 2 indicating both the favourable and unfavourable environments for all the component characters.…”
Section: Resultsmentioning
confidence: 80%
“…Patil (2007) reported the genotypes viz., RPSP 742, EC 138375 and RPSP 732 were high yielder with average stability of genotypes. Kandel et al (2020) reported significant genotypes and genotypes and their interaction for plant height along with genotype CO-4656 which had mean yield that was higher than the overall mean (0.429 t ha -1 ) with parameter of response (b i )=1.16 and parameter of stability (S 2 di)=0.05.…”
Section: Resultsmentioning
confidence: 98%
“…The variance due to pooled deviation was found significant for days to 50% flowering, productive tillers per plant, spikes per panicle, hulling (%). Highly significant differences among genotypes, environments and G x E interaction were reported by Fentie et al [10], Sood et al [11], Ataei and Reza [12] and Kandel et al [13].…”
Section: Resultsmentioning
confidence: 91%
“…* and ** significant at 5 and 1 per cent levels, respectively when Ho: bi = 0 + and ++ significant at 5 and 1 per cent levels, respectively when Ho: bi = 1 Where, bi and S 2 di were regression coefficient and deviation from regression, respectively * and ** significant at 5 and 1 per cent levels, respectively when Ho: bi = 0 + and ++ significant at 5 and 1 per cent levels, respectively when Ho: bi = 1 Patel et al [15] found out significant G × E interaction for grain yield per plant. Kandel et al [13] reported that the genotype CO-4656 had mean yield which was higher than the overall mean (0.429 t/ha), parameter of response (b)=1.16 and parameter of stability (S2di)=0.05. Madhavilatha et al [18] reported average stability for grain yield was found in VR 990 which revealed the wide adaptability of the genotype across different locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation